Interaction with the community (Shi gnouma de bè senekela ka sôrôyiriwa) - International Institute of Tropical Agriculture (International Livestock Research Institute, 2018)
The ninth and the final episode of a radio program series by the Africa RISING program in Bambara dialect that is spoken in southern Mali. In this episode which aired on KAFO KAN radio on 15 December 2017, farmers had general discussions with presenters on various issues related to production of dual-purpose sorghum varieties. This radio program was produced as part of Africa RISING activity - use of Interactive radio to scale-up agriculture and nutrition technologies in Africa RISING Mali.